Impact of Enhancer of Zeste Homolog 2 on T Helper Cell-Mediated Allergic Rhinitis - Hou, Tsung-Yun; Chen, Ming-Rong; Chou, Yu-Ching; Kan, Po-Chieh; Tsai, Yi-Ta; Cha, Tai-Lung (Frontiers in Immunology, 2017)
Enhancer of zeste homolog 2 (Ezh2) has been shown to play a role in the differentiation of T helper (Th) 1 and 2 cells in mice studies using Ezh2-deficient T cells. However, the results have been inconsistent, and the function of Ezh2 in human Th1 and Th2 cell differentiation and its association with disease remains controversial. We measured the expression of Ezh2 in Th1 and Th2 cells in peripheral blood mononuclear cells after acute challenge with house dust mite using flow cytometry in patients with allergic rhinitis and controls. The role of Ezh2 was further explored by adding the p38 inhibitor to see if this affected allergen-induced Th1 and Th2 differentiation. The expression of Ezh2 in the Th1 and Th2 cells was significantly lower in the patients than in the controls, and was negatively correlated with serum IL-17A levels in the patients. Ex-vivo allergen challenge resulted in rapid Th2 cell differentiation, which was negatively associated with the Ezh2 expression in Th2 cells. In contrast, Th1 cell differentiation was positively associated with the Ezh2 expression in Th1 cells. Inhibiting p38 activity increased the expression of Ezh2 in Th2 cells and reduced the number of differentiated Th2 cells. Our findings suggest that Ezh2 expression is potentially associated with allergic rhinitis development.